The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1159/000051949
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Diverticulitis: A Diagnostic Challenge

Abstract: Background: Cecal diverticulitis is frequently indistinguishable from acute appendicitis preoperatively and is sometimes mistaken for carcinoma at laparotomy. The surgeon must be aware of the possibility of diverticulitis of the cecum in the operating room and choose the appropriate treatment. Purpose: Because there is no universal therapeutic approach to these patients, we decided to assess the presenting symptoms, clinical findings, preoperative diagnosis, operative findings determining the proper management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
20
1
2
Order By: Relevance
“…While in other reports the age of patients with right-sided diverticulitis is lower compared to left-sided diverticulitis [2,4,6,9,10,13,19], no significant difference was observed in this study (60.9 years for right-sided vs 63.1 years for sigmoid diverticulitis, p>0.05). The diagnostics for right-sided diverticulitis are similar to those for diverticular disease of the left colon: abdominal ultrasound and CT scan with intravenous contrast medium or colon contrast enema with water-soluble contrast medium will lead to the correct diagnosis in up to 90% [20].…”
Section: Discussioncontrasting
confidence: 92%
“…While in other reports the age of patients with right-sided diverticulitis is lower compared to left-sided diverticulitis [2,4,6,9,10,13,19], no significant difference was observed in this study (60.9 years for right-sided vs 63.1 years for sigmoid diverticulitis, p>0.05). The diagnostics for right-sided diverticulitis are similar to those for diverticular disease of the left colon: abdominal ultrasound and CT scan with intravenous contrast medium or colon contrast enema with water-soluble contrast medium will lead to the correct diagnosis in up to 90% [20].…”
Section: Discussioncontrasting
confidence: 92%
“…Some studies in the literature also demonstrated that right colonic diverticulitis can be correctly diagnosed using radiologic evaluation [15,16]. Without any further imaging modalities such as CT, right-sided diverticulitis, in particular cecal diverticulitis is quite difficult to distinguish from acute appendicitis before surgery based only on clinical presentations, and the percentage of misdiagnosis is over 90% [17,18]. Therefore CT should be considered the diagnostic tool of choice in patients with suspected acute diverticulitis of the colon [8].…”
Section: Discussionmentioning
confidence: 99%
“…Solitary diverticulum of the caecum is a rare and congenital entity [2] and perforation of such a diverticulum was fi rst described by Potiers in 1992. Since then there have been reports from different parts of the world [3][4][5][6][7]. Though perforated appendix in a hernial sac has been reported [8], there has been no report of a perforated caecal diverticulum in a hernial sac.…”
Section: Discussionmentioning
confidence: 99%